Endozoochorus dispersal of aquatic plants: does seed gut passage affect plant perfomance? - Figuerola, Jordi; Santamaría, Luis; Green, Andy J.; Luque, Isabel; Álvarez, Raquel; Charalambidou, Iris (American Journal of Botany, 2005)
The ingestion of seeds by vertebrates can affect the germinability and/or germination rate of seeds. It is, however, unclear if an earlier germination as a result of ingestion affects later plant performance. For sago pondweed, Potamogeton pectinatus, the effects of seed ingestion by ducks on both germinability and germination rate have been previously reported from laboratory experiments. We performed an experiment to determine the effects of seed ingestion by ducks on germination, seedling survival, plant growth and asexual multiplication. Both at the start and end of the winter, seeds were fed to three captive shovelers (Anas clypeata) and planted outdoors in water-filled containers. Plant biomass and its allocation to vegetative parts (shoot and roots), tubers, and seeds were determined in autumn. More duck-ingested seeds than control (uningested) seeds germinated in early winter, but this difference disappeared for seeds planted in late winter, when the treatments were first stratified for 3 mo. None of the variables for measuring seedling survival and plant performance varied between treatments. Under our experimental conditions (no herbivory or competition), ingestion by ducks in early winter resulted in increased performance for seeds surviving gut passage due to enhanced seed germinability, without other costs or benefits for the seedlings Peer reviewed